APLIKASI BANTU ANTRI UNTUK RUMAH SAKIT PENERIMA BPJS - Nurlela Purnama (Universitas Mercu Buana, 2019)
In dealing with the health of the Indonesian public, the government established a BPJS program to assist the community in financing their medical needs, especially for treatment in hospitals receiving BPJS programs. This makes many patients queue at the hospital, the patients are required to queue long and jostled with other patients in one room to wait for treatment. The queue system makes the patient lose a lot of time, fatigue, and risk of contracting with other diseases. Researchers use Design Thinking as a method of solving problems, and an application is designed to make it easier for patients to queue in hospitals. This queuing assist application was tested to validate the solution to two users namely to the hospital and to the patient, based on interviews with the hospital this application could not help because of the problem of congestion that often occurs in big cities in Indonesia, and hospitals in the city have the most BPJS patients. The results of interviews with ten patients and families this application is needed with the consideration that the application is easy to use and will reduce their time waiting for queues to meet with doctors and taking drugs. In this design thinking process, the application of queuing can be a solution because the negative impact of the patient's delay due to congestion is an external impact of queuing problems.